2014
DOI: 10.1007/s11136-014-0854-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life perceived by end-stage renal disease patients under online hemodiafiltration

Abstract: Our results showed that the coexistence of diabetes, gender and erythropoietic disturbances are predictors of HRQOL in patients under OL-HDF and suggest that more attention should be given to woman patients, to the improvement of anemia and to diabetic patients, who are more prone to perceive a worst HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
4
12
1
Order By: Relevance
“…; Moura et al . ). However, there is some controversy whether depression has a direct causal role in the poor results of treatment, or if depression is just a marker of increased associated co‐morbidities and disease severity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Moura et al . ). However, there is some controversy whether depression has a direct causal role in the poor results of treatment, or if depression is just a marker of increased associated co‐morbidities and disease severity.…”
Section: Discussionmentioning
confidence: 97%
“…Depression is a common and serious comorbid condition in patients on dialysis, with prevalence rates estimated between 20% and 44% (Kimmel & Peterson 2005;Watnick et al 2005;Hedayati et al 2006;Kimmel et al 2007). Depression has been associated with greater medical co-morbidity, lower quality of life, decreased survival and decreased adherence to dialysis prescription treatments (Cukor et al 2009;Rosenthal et al 2012;Moura et al 2014). However, there is some controversy whether depression has a direct causal role in the poor results of treatment, or if depression is just a marker of increased associated co-morbidities and disease severity.…”
Section: Gds: Geriatric Depression Scalementioning
confidence: 99%
“…Table). For RRT treatments, KTx recipients reported higher mean generic and specific scores relative to those on dialysis [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] (S2-S4 Tables). Nagaraja et al [44] converted the SF-36 data into SF-6D utility scores and showed a similar relationship; kidney transplantation was associated with better mean SF-6D utility scores relative to HD (0.65± SD: 0.13 vs 0.52± SD: 0.11, respectively).…”
Section: The Kdqol-sf™ Toolmentioning
confidence: 99%
“…As people with these two chronic diseases are known to have competing physical and psychological needs when compared to people with the single condition, there is a need to understand how their complex needs translate into impact on HRQoL and its specific subscales as well as the impact of increasing disease severity. Within this context there is a need for studies across the continuum from early stages of diabetes and CKD through to late stages [8] that seek to identify factors associated with HRQoL particularly those that can be modified [15]. To do this we examined factors associated with HRQoL in patients with co-morbid diabetes and CKD of varying severity who access specialist medical care from tertiary hospitals.…”
Section: Introductionmentioning
confidence: 99%